O Papel da Arquitectura no Envelhecimento Ativo: pela teoria e prática - João Maria da Rocha Ferreira Almeida Barbosa (2022)
The following thesis, through space architectural exercise based on the theory and practical spheres, aims at interpreting architecture's involvement as a piece for a better quality of life. Pointing the problem of ageing as an escalating one, we considered as convenient to look at this "day-to-day" problem. Focusing this research based on this human condition that creates dependency and fragility brought an opportunity to pursue the argument that architecture serves Man. Under this premise, some chapters were developed guiding us through the problem devoted to its analysis, and the conception of a project proposal. We look at the data coming from the place and problematic circumstances around these factors. It is explored the importance of shared living space as well as the specific mechanisms that help merge Man to Man, in space, throughout architecture. In this context it also appears the materialization of the project proposal that reflects the desire to contribute to Matosinhos' Municipality in this area.